2016
DOI: 10.1007/s11764-016-0552-5
|View full text |Cite
|
Sign up to set email alerts
|

Negative information-seeking experiences of long-term prostate cancer survivors

Abstract: Purpose Many prostate cancer survivors have lasting symptoms and disease-related concerns for which they seek information. To understand survivors’ information seeking experiences, we examined the topics of their information searches, their overall perceptions of the search, and perceptions of their health information seeking self-efficacy (i.e., confidence in their ability to obtain information). We hypothesized that negative search experiences and lower health information seeking self-efficacy would be assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…It has been reported that approximately one-third (31.7%) of PCa survivors have negative information-seeking experiences when looking for information. [ 41 ] Our study also showed that information acquisition in the control group was significantly lower compared with the baseline level at the 3-month follow-up.…”
Section: Discussionsupporting
confidence: 63%
“…It has been reported that approximately one-third (31.7%) of PCa survivors have negative information-seeking experiences when looking for information. [ 41 ] Our study also showed that information acquisition in the control group was significantly lower compared with the baseline level at the 3-month follow-up.…”
Section: Discussionsupporting
confidence: 63%
“…Our findings go beyond the physical barrier by showing that people with lower educational attainment and income had more skill barriers, including a lot of effort and frustration during the search and difficulties in understanding the web-based health information. This confirmed the SES disparities in experiences of web-based HISBs identified in our qualitative interview [ 15 ] and studies including patient populations only [ 41 , 42 ]. The findings supported the “Inverse Care Law” [ 43 ], which suggests that the disadvantaged groups are most in need of healthcare but may benefit less from health-related ICTs.…”
Section: Discussionsupporting
confidence: 86%
“…Self‐efficacy in health information seeking is one's confidence in accomplishing health information relevant tasks. As an individual believes in the ability to obtain desired health information, he or she often makes greater efforts and spend more time in searching …”
Section: Introductionmentioning
confidence: 99%